A nonparametric analysis of competitiveness efficiency: The relevance of firm size and the configuration of competitive pillars - Lafuente, Esteban; Leiva, Juan Carlos; Moreno-Gómez, Jorge; Szerb, László (BRQ Business Research Quarterly, 2020)
This study employs a data envelopment analysis (DEA) model with a single constant input to analyze the competitiveness performance of a unique sample of 103 knowledge-intensive business service (KIBS) firms from Hungary, Spain, Colombia, and Costa Rica for the year 2017. Also, we assess how the configuration of competitive pillars-strengths and weaknesses-affects efficiency and how firm size moderates this relationship. The mean efficiency scores by which the competitiveness output can be optimized is 47.43%. The results suggest that the configuration of competitive pillars has important implications for efficiency analyses. For small businesses, competitive-enhancing actions should focus on mitigating competitive weaknesses that are detrimental to efficiency. Also, a configuration of competitive pillars in which one or various competitive strengths prevail is more beneficial for small businesses. Managerial tools such as the proposed competitiveness measure may offer useful information on what strategic actions can contribute to optimize business competitiveness.